Heidegger - Inwood, Michael (Oxford Oxford university press, 1997)
Martin Heidegger (1889-1976) is probably the most divisive philosopher of the twentieth century: viewed by some as a charlatan and by others as a leader and central figure of modern philosophy. Michael Inwood's lucid introduction to Heidegger's thought focuses on his most important work, "Being and Time," and its major themes of existence in the world, inauthenticity, guilt, destiny, truth, and the nature of time. These themes are then reassessed in the light of Heidegger's later work, together with the extent of his philosophical importance and influence. This is an invaluable guide to the complex and voluminous thought of a major twentieth-century existentialist philosopher.About the Series: Combining authority with wit, accessibility, and style, Very Short Introductions offer an introduction to some of life's most interesting topics. Written by experts for the newcomer, they demonstrate the finest contemporary thinking about the central problems and issues in hundreds of key topics, from philosophy to Freud, quantum theory to Islam